Preventing alcohol misuse in young people aged 9-11 years through promoting family communication: an exploratory evaluation of the Kids, Adults Together (KAT) Programme - Segrott Jeremy; Rothwell Heather (BMC, 2011)
Abstract Background Alcohol misuse by young people is an important public health issue, and has led to the development of a range of prevention interventions. Evidence concerning the most effective approaches to intervention design and implementation is limited. Parental involvement in school-based interventions is important, but many programmes fail to recruit large numbers of parents. This paper reports findings from an exploratory evaluation of a new alcohol misuse prevention programme - Kids, Adults Together (KAT), which comprised a classroom component, engagement with parents through a fun evening for families with children aged 9-11 years, and a DVD. The evaluation aimed to establish the programme's theoretical basis, explore implementation processes and acceptability, and identify plausible precursors of the intended long-term outcomes. Methods Documentary analysis and interviews with key personnel examined the programme's development. Classroom preparation and KAT family events in two schools were observed. Focus groups with children, and interviews with parents who attended KAT family events were held immediately after programme delivery, and again after three months. Interviews with head teachers and with teachers who delivered the classroom preparation were conducted. Follow-up interviews with programme personnel were undertaken. Questionnaires were sent to parents of all children involved in classroom preparation. Results KAT achieved high levels of acceptability and involvement among both children and parents. Main perceived impacts of the programme were increased pro-social communication within families (including discussions about harmful parental alcohol consumption), heightened knowledge and awareness of the effects of alcohol consumption and key legal and health issues, and changes in parental drinking behaviours. Conclusions KAT demonstrated promise as a prevention intervention, primarily through its impact on knowledge and communication processes within families, and its ability to engage with large numbers of parents. A key programme mechanism was the classroom preparation's facilitation of parental involvement in the family fun evening. The programme also incorporated features identified in the literature as likely to increase effectiveness, including a focus on harm reduction, interactive delivery, and targeting primary-school-age children. Further research is needed to test and develop programme theory through implementation in different school contexts, and to examine potential longer-term impacts, and the feasibility of large scale delivery.